Food safety management systems: The role of cognitive and cultural biases in determining what is ‘safe enough’ - Manning, Louise; Grant, Jack H. (Trends in food science & technology, 2025)
Food safety management systems (FSMS) are designed and implemented to control, and where possible eliminate, the potential food safety hazards associated with a product, and how food is produced, to ensure compliance with food safety legislation, retailer standards and/or private third-party certification standards. However, the design, validation, implementation and verification of FSMS can be subject to both conscious and unconscious bias that inform risk management and risk acceptance. The aim of this structured review is to firstly consider existing hazard analysis and risk assessment approaches to developing and implementing FSMS, and approaches to defining what is “safe enough’ and, secondly to explore the role of cognitive and cultural biases in decision-making. Cognitive and cultural biases can influence food safety assessment, FSMS design and perceptions, management and acceptance of food safety risk. A better understanding of their influence and how this informs scientific and lay approaches to hazard analysis and food safety risk assessment could provide more insight into how regulators, food business operators, staff and consumers assess and accept food safety risk. [Display omitted] •Stakeholders vary in the mechanisms they use to determine food safety risk.•Hazard analysis and risk assessment processes are influenced by biases.•Cognitive and cultural biases influence perceptions of acceptable levels of risk.•Cognitive and cultural biases inform and frame FSMS design and implementation.•What is ‘safe enough’ can be determined both objectively and subjectively.